Time‐resolved photometry of the high‐energy radiation of M dwarfs with the Star‐Planet Activity Research Cubesat. Issue 4 (14th November 2021) - Ramiaramanantsoa, Tahina; Bowman, Judd D.; Shkolnik, Evgenya L.; Loyd, Robert Oliver Parke; Ardila, David R.; Barman, Travis; Basset, Christophe; Beasley, Matthew; Cheng, Samuel; Gamaunt, Johnathan; Gorjian, Varoujan; Jacobs, Daniel; et al.
Abstract: Know thy star, know thy planet, … especially in the ultraviolet (UV). Over the past decade, that motto has grown from mere wish to necessity in the M dwarf regime, given that the intense and highly variable UV radiation from these stars is suspected of strongly impacting their planets' habitability and atmospheric loss. This has led to the development of the Star‐Planet Activity Research CubeSat ( SPARCS ), a NASA‐funded 6U CubeSat observatory fully devoted to the photometric monitoring of the UV flaring of M dwarfs hosting potentially habitable planets. The SPARCS science imaging system uses a 9‐cm telescope that feeds two delta‐doped UV‐optimized CCDs through a dichroic beam splitter, enabling simultaneous monitoring of a target field in the near‐UV and far‐UV. A dedicated onboard payload processor manages science observations and performs near‐real‐time image processing to sustain an autonomous dynamic exposure control algorithm needed to mitigate pixel saturation during flaring events. The mission is currently halfway into its development phase. We present an overview of the mission's science drivers and its expected contribution to our understanding of star‐planet interactions. We also present the expected performance of the autonomous dynamic exposure control algorithm, a first‐of‐its‐kind onboard a space‐based stellar astrophysics observatory.